Jasa Merin's staff acceptance towards internet banking / Nor Azhana A. Bakar - A. Bakar, Nor Azhana (2011)
Nowadays, Internet banking services are very popular among people to do any transaction such as fund transfer, check balance and many more. This paper project explored the acceptance of Internet banking among Jasa Merin’s staff. The research is done at Jasa Merin office in Kemaman, Terengganu where all the staff become respondent. The aim of this paper is to identify the factor that affecting the acceptance of Internet banking and a data was gathered from the sample of 59 questionnaires. The results of the respondents were analyzed using Statistical Package for the Social Sciences (SPSS) from which the hypothesis were tested and conclusion drawn. The results from the survey indicated that 70.9% accept the usage of Internet banking. However, only 48.1% from the result are explained by all the independent variables and the remaining were unexplained factors and need to be investigate by future researcher for generating better explanation to acceptance of Internet banking. The most influences factor towards dependent variable is privacy with the beta of 0.413, second is security with 0.132 and the last one is ease of use with 0.115.